Clinical researchEvaluation of bone mineral density and bone turnover markers in Egyptian children with juvenile rheumatoid arthritis - Kandil, Manal E.; Mourad, Abbass; El Hamshary, Azza; Hussein, Gehan; Ahmed, Azza; Mawgoud, Sohair Abdel (Archives of Medical Science, 2009)
Introduction: To evaluate bone mineral density (BMD) and levels of bone turnover markers in Egyptian children with juvenile rheumatoid arthritis (JRA), and its relationship with disease-related variables. Material and methods: A case-control study included thirty children having JRA and 25 healthy controls. They were subjected to measurement of BMD of lumbar spines (L2-L4) and femoral neck using dual-energy-X-ray absorptiometry (DXA) with laboratory evaluation of bone turnover markers including serum receptor activator of nuclear factor kB-ligand (RANKL) and osteoprotegerin (OPG). Results: Patients had significantly lower femoral neck BMD than controls (p = 0.02), and it was significantly lower in patients with corticosteroid therapy (p = 0.04). Eight patients (26.7%) and only 2 (8%) controls had low BMD at lumbar spine, while 13 patients (43.3%) and 2 (8%) controls had low BMD at femoral neck. Patients showed significantly higher RANKL, OPG and deoxypyridinolin (p = 0.0001, p = 0.049, p = 0.047), while calcium, osteocalcin, bone-specific alkaline phosphatase and OPG/RANKL ratio were significantly lower in them (p = 0.015, p = 0.031, p = 0.041, p = 0.0001). Patients with normal BMD were significantly taller than patients with low BMD (p = 0.035), while the number of active painful joints and swollen restricted mobility joints were significantly higher in patients with low BMD (p = 0.03, p = 0.02), with no significant difference regarding disease duration and bone turnover markers (p > 0.05). Conclusions: JRA patients had lower BMD, higher frequency of low BMD (more prominent in the femoral neck) and higher OPG and RANKL levels compared with healthy children; suggesting that they may be at risk of developing premature osteoporosis and fractures later in life.